Adaptive super-twisting sliding mode observer based robust backstepping sensorless speed control for IPMSM. (September 2019) - Wu, Shaofang; Zhang, Jianwu; Chai, Benben
Abstract: This paper proposes a higher-order sliding mode observer based robust backstepping control to realize high-performance sensorless speed regulation for the interior permanent magnet synchronous motor (IPMSM). A new robust adaptive super-twisting higher-order sliding mode based observer is proposed to estimate the rotor position. The proposed observer has advantages of sliding chattering reduction and robustness against uncertainties. And, a new robust integral adaptive backstepping control with sliding mode actions is designed to achieve precise speed regulation. The uncertainties with unknown bounds can be stabilized by the sliding mode actions. And both transient and steady performance can be achieved by using the sliding mode and integral actions simultaneously. Then, a sensorless scheme is put forward to by combining the presented observer and the proposed controller. The stability of the observer and controller are verified. Simulation and experiment results validate the proposed approach. Highlights: A robust adaptive super-twisting sliding mode based position observer is proposed for the interior permanent magnet synchronous motor. The observer can reduce sliding chattering and ensure robustness to disturbances against disturbances. A robust integral adaptive backstepping control with sliding mode actions is designed to regulate the motor speed. Disturbances with unknown bound can be stabilized by the sliding mode control. And both transient and steady performance can be achieved by using the sliding mode and integral actions simultaneously. A sensorless scheme is put forward by combining the proposed controller and the presented observer. The stability of the observer and controller are verified.